2016
DOI: 10.1021/acs.est.5b06097
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli, Bacteriophage MS2, and Bacillus Spores under UV/H2O2 and UV/Peroxydisulfate Advanced Disinfection Conditions

Abstract: Ultraviolet light (UV) combined with peroxy chemicals, such as H2O2 and peroxydisulfate (PDS), have been considered potentially highly effective disinfection processes. This study investigated the inactivation of Escherichia coli, bacteriophage MS2, and Bacillus subtilis spores as surrogates for pathogens under UV/H2O2 and UV/PDS conditions, with the aim to provide further understanding of UV-based advanced disinfection processes (ADPs). Results showed that one additional log of inactivation of E. coli was ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(102 citation statements)
references
References 36 publications
5
97
0
Order By: Relevance
“…[41] The addition of H 2 O 2 largely also improves UV disinfection processes.I nt he UV disinfection of surfacew ater and wastewater from am unicipal treatment plant, for instance, the inactivation of Escherichia coli bacteria, Bacilluss ubtilis spores, and MS2 bacteriophage viruses proceeded best when UV irradiation was coupled with optimized doses of H 2 O 2 and peroxydisulfate (PDS,S 2 O 8 2À ). [42] Although UV-only treatment performed well with regardt oEscherichia coli,a ny improvement for H 2 O 2 or PDS was marginal, whereas UV/H 2 O 2 far outperformed UV/ PDS with regard to UV-resistant MS2, and only UV/H 2 O 2 succeeded in deactivating Bacillussubtilis.…”
Section: Emerging Usesmentioning
confidence: 95%
“…[41] The addition of H 2 O 2 largely also improves UV disinfection processes.I nt he UV disinfection of surfacew ater and wastewater from am unicipal treatment plant, for instance, the inactivation of Escherichia coli bacteria, Bacilluss ubtilis spores, and MS2 bacteriophage viruses proceeded best when UV irradiation was coupled with optimized doses of H 2 O 2 and peroxydisulfate (PDS,S 2 O 8 2À ). [42] Although UV-only treatment performed well with regardt oEscherichia coli,a ny improvement for H 2 O 2 or PDS was marginal, whereas UV/H 2 O 2 far outperformed UV/ PDS with regard to UV-resistant MS2, and only UV/H 2 O 2 succeeded in deactivating Bacillussubtilis.…”
Section: Emerging Usesmentioning
confidence: 95%
“…Subsequently, the culture was centrifuged at 6000 rpm for 10 minutes to harvest the bacteria which were resuspended in 50 mM Na 2 SO 4 . This step was repeated three times to achieve bacterial suspension without any nutrients and metabolites from the cells [24]. E. coli suspension was stocked in 4 °C for further use.…”
Section: Inactivation Testsmentioning
confidence: 99%
“…In terms of hydrogen peroxide generation, it could be accumulated without of Fe 2+ but it seemed not to contribute to disinfection (Figure 2a) as only approximate 3.5 mg/L H 2 O 2 was detected. It was still far below the level needed for disinfection [24]. Therefore it was concluded that the radical oxidative species (e.g.,…”
Section: Figure 2 Is Herementioning
confidence: 99%
“…Peroxydisulfate (or simply persulfate, S2O8 2-) is being increasingly used in advanced oxidation processes for treatment of wastewater and industrial waste, and in situ chemical oxidation (ISCO) for remediation of contaminated soil and groundwater (Huling et al, 2006;Tsitonaki et al, 2010;Deng and Ezyske, 2011;Siegrist et al, 2011;Drzewicz et al, 2012;Ahn et al, 2013;Yang et al, 2014;Sun et al, 2016). In these applications, persulfate is activated into sulfate and hydroxyl radicals (SO4 •and • OH), powerful oxidants that can oxidize a wide range of organic contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…In these applications, persulfate is activated into sulfate and hydroxyl radicals (SO4 •and • OH), powerful oxidants that can oxidize a wide range of organic contaminants. Common persulfate activators include heat Johnson et al, 2009;Constanza et al, 2010), ultraviolet light (Yang et al, 2014;Sun et al, 2016), dissolved metals and metal oxides (Anipsitakis and Dionysiou, 2004;Ahmad et al, 2010;Sra et al, 2010;Drzewicz et al, 2012;Ahn et al, 2013;Liu et al, 2014), and alkaline solutions (Singh and Venkatarao, 1976;Furman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%